DOI: 10.5353/th_b3122266
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase deficient mice develop nephrogenic diabetes insipidus

Abstract: Aldose reductase (ALR2) is thought to be involved in the pathogenesis of various diseases associated with diabetes mellitus, such as cataract, retinopathy, neuropathy, and nephropathy. However, its physiological functions are not well understood. We developed mice deficient in this enzyme and found that they had no apparent developmental or reproductive abnormality except that they drank and urinated significantly more than their wild-type littermates. These ALR2-deficient mice exhibited a partially defective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In part, this might be because the relatively low AR expression in the mouse has allowed it to develop other defenses. Nerve conduction velocity, which is reduced in diabetic rats by the overexpression of AR, remains completely normal in the AR knockout mouse 82. Similarly, cardiac contractile function appears normal with AR genetic deletion, an observation consistent with the lack of change in heart function with AR pharmacological inhibition 25, 41, 63, 86, 87.…”
Section: Physiological Functions Of Arsupporting
confidence: 56%
See 2 more Smart Citations
“…In part, this might be because the relatively low AR expression in the mouse has allowed it to develop other defenses. Nerve conduction velocity, which is reduced in diabetic rats by the overexpression of AR, remains completely normal in the AR knockout mouse 82. Similarly, cardiac contractile function appears normal with AR genetic deletion, an observation consistent with the lack of change in heart function with AR pharmacological inhibition 25, 41, 63, 86, 87.…”
Section: Physiological Functions Of Arsupporting
confidence: 56%
“…Despite the fact that AR is absent from all tissues, these genetically-engineered mice have minimal phenotype; they have normal structural, biochemical, reproductive and physiological properties. Consistent with the known osmoregulatory function of AR, their only abnormality is mild polyuria compensated by mild polydipsia 82. Urine and blood divalent cation concentration was also slightly altered, but it remains unclear if the changes were secondary to mild chronic diuresis or if AR plays a role in maintaining systemic divalent cation levels 83.…”
Section: Physiological Functions Of Armentioning
confidence: 70%
See 1 more Smart Citation
“…However, these rats were not able to produce littermates, indicating their reproductive abnormalities. In contrast, AKR1B1 null mice showed no apparent growth and reproductive abnormalities [24]. Since we failed to generate littermates, we examined the protective effect of knockdown of AKR1B1 against hyperglycemic cataractogenesis in rat lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that AR‐deficient mice created by genetic manipulation exhibit no obvious phenotypes except for a partially defective urine‐concentrating ability with renal structural abnormalities (Ho et al . ; Yang et al . ).…”
mentioning
confidence: 99%